The management of bacterial conjunctivitis - Kiełczewska, Anna; Kiełczewska, Aleksandra; Szcześniak, Grzegorz (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Bacterial conjunctivitis, a common eye disease characterized by inflammation of the conjunctiva, poses a major challenge in clinical practice due to its prevalence, diverse etiology and the need for effective pharmacological treatment. The conjunctiva is constantly exposed to the adverse effects of various external and internal factors. This review is devoted to the pharmacological treatment of bacterial conjunctivitis, with a focus on the most common causative agents. Materials and Methods: A comprehensive survey of articles published in scientific journals was conducted via PubMed and Google Scholar online research platforms. Articles were searched by entering keywords in the appropriate configuration: “bacterial conjunctivitis,” ‘pharmacotherapy,’ ‘bacterial,’ and ”antibiotics.” Description of current knowledge: Emerging research has shown that the choice of antibiotic for the treatment of bacterial conjunctivitis depends primarily on the etiology and severity of the infection. Summary: Antibiotic therapy is an effective tool in the treatment of bacterial conjunctivitis, but its use requires consideration of etiology, severity of infection and potential risk of resistance. Collaboration between ophthalmologists and microbiologists is necessary for the optimal management of this condition. Acute bacterial conjunctivitis is a prevalent eye condition that requires prompt and appropriate pharmacological management.